2004
DOI: 10.1097/01.pcc.0000113261.13338.c3
|View full text |Cite
|
Sign up to set email alerts
|

Study of protein C, protein S, and antithrombin III in hypoxic newborns*

Abstract: In this study, we evaluated the effect of asphyxia on the physiologic inhibition system of coagulation in neonates. Care providers should suspect hypoxia resulting from any obstructed labor and perform the necessary laboratory investigations for coagulation, including antithrombin III, protein C, and protein S levels, to help prevent thromboembolic accidents in asphyxiated neonates, including disseminated intravascular coagulation, necrotizing enterocolitis, and intracranial hemorrhage. Based on the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 11 publications
1
15
1
Order By: Relevance
“…Hypoxia-ischaemia might play a role in activation of thrombogenesis, as it decreases physiologically inhibiting anticoagulants, including antithrombin III, proteins C and S resulting in hypercoagulability 21 22. Adhami et al 23 found that ischaemia-hypoxia is a rapid and powerful stimulus for spontaneous coagulation in mice that underwent the Levine/Vannucci procedure, mimicking perinatal hypoxic-ischaemic brain injury 24.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-ischaemia might play a role in activation of thrombogenesis, as it decreases physiologically inhibiting anticoagulants, including antithrombin III, proteins C and S resulting in hypercoagulability 21 22. Adhami et al 23 found that ischaemia-hypoxia is a rapid and powerful stimulus for spontaneous coagulation in mice that underwent the Levine/Vannucci procedure, mimicking perinatal hypoxic-ischaemic brain injury 24.…”
Section: Discussionmentioning
confidence: 99%
“…It may be useful to measure levels of antithrombin III, protein C, and protein S-components of the physiological inhibition pathway of coagulation-because these are decreased in HIE. 26 Other possible findings include raised urea and creatinine and deranged electrolytes owing to acute renal failure; raised alanine aminotransferase, raised aspartate aminotransferase, and deranged clotting owing to liver dysfunction. Blood gases often show a hypoxic picture, with raised lactate and metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…8 Intrauterine fetal hypoxia also triggered coagulation disturbances in asphyxiated neonates. 9 Thus, the challenge is not only to stabilize the mother as early as possible but also expediate the delivery of the hypoxic and distressed fetus. 10 The situation may become more difficult if the platelet count in the mother starts falling below a critical limit initiating DIVC, a serious condition.…”
Section: Discussionmentioning
confidence: 99%